Clinical Spectrum, Geographical Variability of COVID-19, and its Implications - Siam, Md. H. B.; Al Mosabbir, Abdullah; Nishat, Nahida H.; Ahmed, Ahsan; Hossain, Mohammad Sorowar (Coronaviruses, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has triggered a worldwide unprecedented public health crisis. Initially, COVID-19 was considered a disease of the respiratory system, as fever and at least one respiratory symptom was used to identify a suspected COVID-19 case. But there are now numerous reports of COVID-19 patients presenting with myriads of extrapulmonary symptoms, however, a substantial number of patients are asymptomatic. Additionally, there are significant clinical and epidemiological variations of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infection across different geographical locations. The updated research, thus, challenges the existing surveillance system that is mainly based on fever and respiratory symptoms. As countries are coming out of lockdown to save economic fallout, a revised surveillance strategy is required to effectively identify and isolate the infected patients. Besides, since developing countries are becoming the new epicenters of pandemic and there are limited resources for RT-PCR based tests, documenting the clinical spectrum can play a vital role in the syndromic clinical diagnosis of COVID-19. A plethora of atypical symptoms also aids in guiding better treatment and remains as a source for further research. It is, therefore, crucial to understand the common and uncommon clinical manifestations of SARS-COV-2 infection and its variability across different geographic regions.
Keywords: asymptomatic